The Spiritual Wisdom of the Gospels for Christian Preachers and Teachers, 1-3 Vols - Kavattu, Siby (Asian Horizons, 2011)
John Shea, The Spiritual Wisdom of the Gospels for Christian Preachers and Teachers, 1-3 Vols, Bangalore: Asian Trading Corporation, 2010 (reprinted), Pages: A: xx + 332, B: vi + 281, C: vi+ 330. ISBN: 81-7086-550-6